Spatial and Multilevel Analysis of Unscheduled Contraceptive Discontinuation in Ethiopia: Further analysis of 2005 and 2016 Ethiopia Demography and Health Surveys - Tamirat, Koku Sisay; Nigatu, Solomon Gedlu; Tesema, Getayeneh Antehunegn; Sisay, Malede Mequanent; Tessema, Zemenu Tadesse (Frontiers in Global Women's Health, 2023)
Abstract Background: Unscheduled discontinuation of contraceptives is a public health problem among reproductive-aged women. Particularly, it is associated with unwanted pregnancies that lead to maternal and child mortality, but little is known about the spatial distribution of the problem. Therefore, this study aimed to assess the spatial distribution and associated factors of unscheduled contraceptive discontinuation in Ethiopia. Method: This study used secondary data from the Ethiopia Demography and Health Survey (EDHS) data of 2005 and 2016. The study population was women who used contraceptives in the preceding five years before the survey. A total of 2327 and 3858 eligible women were included in the final analysis of the 2005 and 2016 EDHS. For the spatial analysis, both the 2005 and 2016 EDHS data were analyzed using ArcGIS version 10.7, while for multilevel regression analysis, the 2016 EDHS data were used for multilevel analysis. The final model reported an adjusted odds ratio (AOR) with a 95% Confidence Interval (CI) and a 0.05 p-value was used to declare statistical significance. Result: This study revealed that unscheduled discontinuation of contraceptives varied geographically, and hotspots were detected in the central, north, and eastern parts of Ethiopia. Moreover, diploma and higher education (AOR=1.40; 95%CI: 1.01 1.95), urban residence (AOR=1.37; 95%CI: 1.08 1.72), history of termination of pregnancy (AOR=1.47; 95%CI: 1.14 1.94), married women (AOR=10.79; 95%CI: 6.98 16.69), separated/divorced women (AOR=1.54: 95%CI: 1.07 2.30), 2-4 number of children (AOR=1.46; 95%CI: 1.15 1.84), and involvement in the decision-making process of contraceptive use (AOR=39.26; 95%CI: 28.84 53.45) were factors associated with unscheduled discontinuation of contraceptive. Conclusion: This study revealed that unscheduled discontinuation of contraceptive distribution was significantly clustered in the central, north, and eastern parts of Ethiopia in both surveys. The magnitude of unscheduled contraceptive discontinuation increased from 2005 to 2016. The finding underscores further interventions such as the availability of multiple mixed methods and improvement of women’s decision-making in contraceptive methods choice and utilization are needed in hotspot areas of Ethiopia.